ANALISIS KELAYAKAN FINANSIAL INDUSTRI NUGGET IKAN NILA (Oreochromis niloticus) DI BANDAR LAMPUNG - Anisa Yustiana (Universitas Halu Oleo, 2020)
Nila fish has the potential to be developed into the nilafish nugget industry seen from the availability and affordable price of nilafish. From the forecasting of the availability of nilafish in the Bandar Lampung area, in 2023 the nilafish production is predicted to reach 23.96 tons / year and will increase every year. The purpose of this study was to determine the feasibility analysis of the nilafish nugget industry. The data analysis method used in this research is to use business feasibility analysis (PBP, NPV, BCR, IRR). The assumption in the financial analysis that nilafish raw material is used as much as 43 kg / day or 12900 kg / year, the price of nilafish nuggets is Rp. 37,000 / pack, in one year there are 300 production days. The establishment of the nilafish nugget industry was declared feasible because the NPV was positive, namely Rp. 327,717,403, IRR was greater than the bank interest rate factor of 12%, which was 17.03%, the Net B / C value was greater than 1, namely 1.329 and the Payback Period for 4.07 years.